2009
DOI: 10.1007/s10552-009-9390-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary change among breast and colorectal cancer survivors and cancer-free women in the Norwegian Women and Cancer cohort study

Abstract: Cancer survivors showed little change toward cancer-preventive guidelines, although more advanced stage and being more than 2.4 years post diagnosis was associated with greater change in diet and smoking behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 36 publications
5
59
0
Order By: Relevance
“…Among them, the decrease in vegetable intake was about 102 g/d (>1 serving of 80 g). Previous studies generally observed an increase in vegetable intake among cancer survivors 15, 20, 21, 22, 23, 24, 26, 28. However, most of them were based on qualitative and/or retrospective data.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Among them, the decrease in vegetable intake was about 102 g/d (>1 serving of 80 g). Previous studies generally observed an increase in vegetable intake among cancer survivors 15, 20, 21, 22, 23, 24, 26, 28. However, most of them were based on qualitative and/or retrospective data.…”
Section: Discussionmentioning
confidence: 89%
“…Only 3 studies quantified nutrient intake variations between before and after diagnosis 20, 22, 27. They rather suggested a decrease in fatty acids and an increase in vitamin intakes, however, two of these studies were retrospective and the other focused on breast and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that women with breast cancer quit smoking more often than cancer-free women, while no signifi cant changes in alcohol consumption or BMI were observed. Beyond the scope of the study by Skeie et al (2009), further evidence is needed to identify the types of changes that women with breast cancer make compared to cancer-free women also in subgroups of women with specifi c characteristics and also evidence is needed on the treatment factors that characterise those women with breast cancer who makes the health behaviour changes in order to focus public health interventions.In this prospective study, we compared changes in BMI, alcohol and tobacco consumption following a breast cancer diagnosis in women with changes in cancer-free women. We hypothesised that women with breast cancer would make signifi cantly more behavioural changes to comply with the recommendations of the Danish National Board of Health (www.sst.dk) with regard to alcohol consumption [women should not consume more than 14 alcoholic beverages (1 drink is approximately 12 g alcohol) per week], weight control (BMI ϭ 18 -25 kg/m 2 ) and tobacco use (tobacco cessation) than cancer-free women.…”
mentioning
confidence: 99%